Hercules in Venice: Aldus Manutius and the making of Erasmian humanism - Margolis, O (Warburg Institute, 2019)
A famous portrait of Erasmus by Hans Holbein depicts the scholar with his hands resting on a volume identified as his ‘Herculean Labours’. Erasmus associated this adage with the effort expended and ingratitude encountered by the philologist, and made it central to his self-presentation. In this article, its origins are traced to Erasmus’s encounter with Aldus Manutius, the Venetian printer-humanist who published his Adagia in 1508. The impact of Aldus on Erasmus is shown to be significant, affecting his entire ideology of humanism, including its relationship to print and its religious purpose. This article challenges distinctions between the Italian and the Northern Renaissance that are unhelpful for understanding Erasmus’s development. In light of its findings, it also proposes a new interpretation of Holbein’s painting.